2002
DOI: 10.1890/0012-9615(2002)072[0113:sgmasb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

SYMPATRIC GROWTH MORPHS AND SIZE BIMODALITY IN THE GREEN SEA URCHIN (STRONGYLOCENTROTUS DROEBACHIENSIS)

Abstract: Green sea urchins (Strongylocentrotus droebachiensis) have been a dominant structuring force in boreal, hard-bottom communities and recently have become an important fishery. Despite these roles, relatively little is known about the age, growth, and demographics of field populations. To begin to address these issues, we systematically sampled urchins during 1997 and 1998 at two sites (Allen Island [AI] and Schoodic Peninsula [SP]) in the Gulf of Maine, USA. Basic demographic information (density and size struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 72 publications
(173 reference statements)
0
12
0
1
Order By: Relevance
“…Genetic analysis was not performed on urchins used in this study or in the Pawson & Miller (1982), Grosjean et al . (1996) or Vadas et al . (2002) studies.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis was not performed on urchins used in this study or in the Pawson & Miller (1982), Grosjean et al . (1996) or Vadas et al . (2002) studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several workers hypothesize that migration explains the difference in the size structure of Strongylocentrotus droebachiensis between barrens and kelp bed habitats (Propp 1977, Meidel & Scheibling 1998, Vadas et al 2002. Since urchins on barrens can move up to 5 m per day, and 11 m in 3 d, they should easily be able to cover the distance between barrens and shallow water kelp beds.…”
Section: Discussionmentioning
confidence: 99%
“…The kelp habitat and, thus, most of the sea urchin predators that live associated with kelp have disappeared, leaving the sea urchin populations more or less undisturbed. Sea urchins may live for many years (Russell 1998;Vadas et al 2002;Ebert & Southon 2003), but the fact that the barren ground has lasted for almost 40 years in Norwegian waters indicates that recruitment to the adult population is needed in order to sustain the high population density. However, the survival of post-settlement juveniles is probably sufficient for maintaining high population density on the barren grounds (Christie & Rueness 1998;Hereu et al 2004).…”
Section: The Barren Ground Statementioning
confidence: 99%
“…Consequently, the condition of adult urchins is sub-optimal and mortality tends to be high (Sivertsen 1997a;Christie & Rueness 1998). Christie & Rueness (1998) suggested, therefore, that barren ground populations depend on regular recruitment to prevent a population crash, but this idea is being debated by other authors, who suggest that urchin populations on barrens grounds only need occasional recruitments due to a long life span (Sivertsen 1997b;Vadas et al 2002). Sivertsen (2006) suggested that recruitment strategies may differ with latitudes, but this has not been studied by repeated sampling of recruitment and mortality between years.…”
Section: The Barren Ground Statementioning
confidence: 99%